The early gut microbiome could protect against severe retinopathy of prematurity - Skondra, Dimitra (J AAPOS, 2020)
In this study, 6 infants with type-1 retinopathy of prematurity (ROP) were compared with 4 high-risk preterm neonates without any ROP but similar baseline neonatal comorbidities. The infants with type-1 ROP showed significant enrichment of Enterobacteriaceae at 28 weeks’ postmenstrual age. Several metabolic pathways, including several amino acid metabolism pathways, were enriched in gut microbiota of infants without ROP. Based on these findings, we posit a possible association between early gut microbiome profile and ROP pathogenesis. Furthermore, it is possible that absence of Enterobacteriaceae overabundance, in addition to enrichment of amino acid biosynthesis pathways, may protect against severe ROP in high-risk preterm infants.